Impact of ESG on Corporate Financial Performance : pharmaceutical industry - Mazurok, Anastasiia; Houska, Daniel; Moravec, Tomáš, 1983-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
With climate change becoming a pressing issue, the focus on sustainability has intensified in recent years. This has resulted in an upsurge of interest among capital investors to invest more sustainably. Moreover, there is a growing desire among stakeholders, regulators, and citizens to learn about how sustainability reporting can lead to positive business outcomes. Sustainable investments can be costly, making it imperative for investors to examine whether such investments can have a constructive influence on a company's financial performance. The pharmaceutical sector is one of the significant players when it comes to sustainability investment. This thesis examines the impact of corporate sustainability performance on corporate financial performance for European pharmaceutical market. The study utilises data from 42 publicly traded pharmaceutical companies over a four-year period (2019-2022), that was retrieved from Refinitiv Eikon, a financial database managed by Refinitiv. Sustainability performance is measured using ESG scores while corporate performance is represented by ROA, ROE and Tobin's Q. Several regression analyses have been conducted using data from Eikon on pharmaceutical companies from 14 European countries. The examination of various ESG pillars was conducted in addition to the overall ESG scores.
Vedoucí práce: Daniel Houska
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses